Diverse associations between adiposity and blood pressure among 80,000 multi-ethnic Chinese adults - Jiayi Chen; Haojiang Zuo; Xinyu Wu; Yuan Zhang; Qiang Tan; Zhimiao Yu; Ciren Laba; Yongyue Pan; Jianzhong Yin; Feng Hong; Peibin Zeng; Xing Zhao (BMC, 2023)
Abstract Background Adiposity is widely recognized as one of the risk factors for high blood pressure (BP) and increasing adiposity is associated with elevated BP. However, which measures of adiposity could be most strongly associated with BP in multi-ethnic population remains uncertain, giving rise to implications that population-based adiposity measures could be necessary. Methods 80,000 multi-ethnic adults recruited from 5 provinces across Southwest China during 2018 ~ 2019 were studied. Multiple linear regression was applied to investigate the associations of systolic blood pressure (SBP) with: (1) two measures of general adiposity, body mass index (BMI) and height-adjusted weight; and (2) three measures of central adiposity, waist circumference (WC), hip circumference (HC) and waist hip ratio (WHR). Results Two distinct population-specific patterns were identified, as "BMI to SBP" and "WC to SBP". 90% of the participants fall into "BMI to SBP" pattern, in which the associations of SBP with BMI were independent of WC, and SBP-WC associations were considerably decreased by adjustment for BMI. And in this pattern, 10 kg/m2 greater BMI was associated with 11.9 mm Hg higher SBP on average. As for the rest population (Han males in Yunnan and Tibetans in Lhasa), they are suited for "WC to SBP" pattern, 10 cm wider WC was associated with 3.4 mm Hg higher SBP. Conclusion Our results indicated that when selecting proper predictors for BP, population-specific adiposity measures are needed, considering ethnicity, sex and residing regions. A better understanding of adiposity and BP may better contribute to the potential clinical practices and developing precision application strategies.